2008
DOI: 10.1158/0008-5472.can-07-0988
|View full text |Cite
|
Sign up to set email alerts
|

A Macrophage Gene Expression Signature Defines a Field Effect in the Lung Tumor Microenvironment

Abstract: One area of intensive investigation is to understand complex cellular and signaling interactions in the tumor microenvironment. Using a novel, although straightforward, microarray approach, we defined a gene expression signature from the lung tumor microenvironment in the murine A/J-urethane model of human lung adenocarcinoma. The tumor microenvironment is reflected by the composition of the cell types present and alterations in mRNA levels, resulting in a ''Field Effect'' around the tumor. The genes composing… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
1
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 47 publications
1
32
1
2
Order By: Relevance
“…The tobacco smoking-induced changes in gene expression and cellular functions are not confined to the pulmonary airway epithelium but have also been reported in the nasal and buccal epithelium (38,39), alveolar macrophages (40,41), and peripheral blood (42). These findings are consistent with the previously presented hypotheses regarding the systemic inflammatory process operative in patients with COPD as well as in those with lung cancer.…”
Section: The Field Cancerization Effectsupporting
confidence: 89%
“…The tobacco smoking-induced changes in gene expression and cellular functions are not confined to the pulmonary airway epithelium but have also been reported in the nasal and buccal epithelium (38,39), alveolar macrophages (40,41), and peripheral blood (42). These findings are consistent with the previously presented hypotheses regarding the systemic inflammatory process operative in patients with COPD as well as in those with lung cancer.…”
Section: The Field Cancerization Effectsupporting
confidence: 89%
“…Likewise, host cells in microenvironment may induce genetic changes and clonal selection in tumor cells that generates a subpopulation of tumor cells with the capability to invade into the surrounding tissue. 25,26 Many recent studies support the first hypothesis; for example, Stearman et al 27 reported that macrophages in lung tumor environment displayed a unique gene expression signature suggesting a role in promoting tumor metastasis. Richardson et al 28 conducted experiments to compare expression profiles in the 4 major components of microenvironment: tumor epithelium, tumor associated stroma, normal epithelium and normal stroma using human prostate cancer specimens.…”
Section: Discussionmentioning
confidence: 87%
“…We found that MMP19 gene expression is modestly increased compared with histologically normal tissue adjacent to the tumor. So-called "field effects," the concept that suggests that cells in proximity to cancer cells are premalignant and should exhibit at least some, but not all, of the genetic alterations that are present in the fully developed cancer (49)(50)(51)(52), may explain the only modest differences in MMP19 expression between tumor and adjacent "normal" tissue. Further study is necessary to elucidate extracellular cues that may lead to increased expression of MMP19.…”
Section: Discussionmentioning
confidence: 99%